Smart Farm Security System Powered by Solar Panels - Bakeri, Muhammad Halimi Zuhdi Bakeri; Bakar, Lilywati (Progress in Engineering Application and Technology, 2023)
One of the economic resources that are currently in great demand is in agriculture. Given that crops and cattle are the basic ingredients in food, their huge demand cannot be disputed any longer. Additionally, farmers utilize high-tech and costly agricultural equipment to facilitate their job, advance the agricultural industry, and improve the quantity and quality of the produce. This project is created specifically to assist farmers in protecting their farm from intruders like wild animals and criminals. This concept is innovative since it includes a solar system as a power source together with security tools including an electric fence, motion sensor, camera, and IoT system. If animals or evil people try to breach the fence, they will receive an electric shock, which will stop them in their tracks and serve as a deterrence to future intrusions. Additionally, an LED that serves as a warning lamp if the fence is struck by something is mounted on each fence post. The motion sensor then uses the IoT system attached to the phone to deliver a warning message to the phone when it detects the movement of intruders in the farm area. The camera simultaneously records movies and takes pictures of the area to be used as proof. This project combines a farm prototype, is controlled by ESP32, and is displayed and demonstrated via an IoT application. Last but not least, this security system is designed for farms using solar as a power supply to maintain environmental sustainability. This project helps farmers to protect their crops from destruction and thieves.